1997
DOI: 10.1007/bf02931968
|View full text |Cite
|
Sign up to set email alerts
|

Influence of Behavioral and Environmental Factors on the Development of Obesity in Three-year-old Children —A Case-Control Study Based on Toyama Study—

Abstract: Obesity in children seems to be a risk factor for chronic diseases in adulthood. From the viewpoint of preventive medicine, factors influencing the development of obese children should be removed early in life.The purpose of this study was to the elucidate relationship between obesity in 3-year-old children and both behavioral and environmental factors by conducting a casecontrol study. Subjects were selected from the Toyama study. Matched-pair comparisons were performed between obese children whose Kaup's ind… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
39
0

Year Published

1999
1999
2017
2017

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 14 publications
(41 citation statements)
references
References 6 publications
2
39
0
Order By: Relevance
“…Increased birth weight was associated with childhood obesity , particularly birthweights >85th and >90th percentiles and birthweights ≥2.5 kg , ≥3 kg , ≥3.5 kg , ≥4 kg , and >4.5 kg . In addition, studies identified rapid weight gain in the first year of life as well as high infant weight as risk factors.…”
Section: Resultsmentioning
confidence: 98%
See 1 more Smart Citation
“…Increased birth weight was associated with childhood obesity , particularly birthweights >85th and >90th percentiles and birthweights ≥2.5 kg , ≥3 kg , ≥3.5 kg , ≥4 kg , and >4.5 kg . In addition, studies identified rapid weight gain in the first year of life as well as high infant weight as risk factors.…”
Section: Resultsmentioning
confidence: 98%
“…Obesity in both parents was identified as a risk factor for childhood obesity in nine studies whereas seven studies found that obesity in either parent was a risk factor . In terms of paternal weight, five studies reported associations between paternal BMI and childhood obesity, and 16 studies found associations between paternal and childhood obesity. Regarding pre‐partum maternal weight, three studies found relationships between BMI and childhood obesity, and seven studies reported associations between maternal obesity and childhood obesity.…”
Section: Resultsmentioning
confidence: 99%
“…This pattern, however, was only observed in crude analyses and was not statistically significant after adjustment. The relationship between maternal employment and early childhood overweight has been investigated in three studies from Japan 20,24,30) , all of which were based on the same birth cohort born in 1989 in Toyama Prefecture. These studies, however, provided only crude estimates, without considering maternal working hours.…”
Section: Discussionmentioning
confidence: 99%
“…In the present study, we restricted the analysis to preschool children aged three years or more in line with previous studies on early childhood overweight 5,7,14,[19][20][21][22][23][24][25] .…”
Section: Study Design and Participantsmentioning
confidence: 99%
“…68 Similarly, among 261 1-5 yold Mescalero children in New Mexico, the OR for obesity (weight-for-height 495th percentile) among children with a birthweight greater than 4000 g (compared to 2000-2999 g) was 4.4 (95% CI 1.3-15.4) even after adjusting for age, sex and maternal obesity (obtained from medical records of her nonpregnant weight and height). 69 There was some indication in the National Study of Health and Growth data 66 that the effect of birthweight on weightfor-height diminished with age -this might explain why the studies in children have found an independent effect of birthweight over parental BMI on risk of obesity, while most of the studies in adults have not.…”
Section: à2mentioning
confidence: 97%